Expert Systems as the Basis of Decisions in the Knowledge Society; MATEC Web of Conferences; Vol. 155 : Information and Measuring Equipment and Technologies (IME&T 2017) - Kvesko S. Svetlana; Kornienko A. A. Anna Anatolievna; Kvesko B. Bronislav; Chicherina N. V. Natality Viktorovna (2018, 2018)
Title screen